Fatal acute-on-chronic liver failure following camrelizumab for hepatocellular carcinoma with HBsAg seroclearance: a case report and literature review - Li, Fenghui; Wang, Tao; Tang, Fei; Liang, Jing (Frontiers in Medicine, 2023)
In the last few years, immune checkpoint inhibitors (ICIs) have become major therapeutic agents for the treatment of advanced hepatocellular carcinoma (HCC). However, immunotherapy can activate hepatitis B virus (HBV), and immune clearance may lead to liver failure and even life-threatening conditions. Here we report a case of HCC with HBV-related cirrhosis that caused severe liver injury and rapidly progressed to fatal acute-on-chronic liver failure (ACLF) after only once application of camrelizumab; the patient underwent serological conversion of hepatitis B surface antigen (HBsAg) with liver injury. The patient’s condition progressed rapidly. We added corticosteroids and applied plasma dialysis, along with tenofovir alafenamide (TAF) to control HBV. However, the patient eventually died of liver failure. To our knowledge, there are few reports of HBsAg clearance due to ICIs accompanied by fatal acute-on-chronic liver failure shortly after ICIs initiation. These results suggest that ICIs can cause fatal liver injury in a short term; in patients with chronic HBV infection, ICIs use may promote serological conversion of HBsAg.